Communication Strategy of Start FM Panyabungan's Ramadan Blessings Islamic Broadcast to Increase the Attractiveness of Broadcast Programs - Nurul Adawiyah Pulungan; Marlina; Desiana (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the communication strategies implemented by Radio Start FM Panyabungan to enhance the appeal of its Islamic religious programs, particularly the Ramadhan Berkah program. The program is held during the month of Ramadan as a means of conveying religious messages and spiritual guidance to the community through radio. The study employed qualitative methods with data collection techniques including interviews, observation, and documentation. Informants in this study consisted of broadcasters, program producers, and active listeners. The data obtained were then analyzed to determine the communication strategies used in program implementation. The results indicate that the success of the Ramadhan Berkah program is supported by several communication strategies, including presenting material that is appropriate to the community's needs, using simple and easy-to-understand language, involving resource persons with religious competence, and utilizing social media and direct interaction with listeners during the broadcast. In addition, determining the broadcast schedule to coincide with important times during Ramadan, such as before breaking the fast and during the pre-dawn meal, also increases public interest in listening to the program. The findings of this study demonstrate that the implementation of appropriate communication strategies can increase listener interest in Islamic religious broadcasts while strengthening the role of radio as a medium for disseminating Islamic values that is adaptive to the development of digital technology. It is hoped that this research can be used as a consideration for broadcasting institutions in developing more effective and popular Islamic preaching programs.